Evaluated possibility of increasing the capacity channel using technology MIMO (Damascus University Journal for engineering sciences, 2023)
Tropospheric communications provide a good solution alternative for beyond- Line-of –Sight (b-Los) communication because it can provide reliable high data rate applications, therefore, the main target of this research is to achieve a  high transfer data rate in tropospheric channel.She is suffer from high path losses, they are  all due the high path length and scattering and, we have proposed to use MIMO technology with lowering  the radiation beamwidth of the used reflecting antennas that provide high gain and spread delay time and less path loss, taking into account the conditions of the non-homogeneities and the time differences of the channel.This research  provides an analytical  study of the troposphreric channel using the MIMO technology to increase its capacity, and finding the transmission data rate of in the tropospheric channel according to signal to noise ratio changies and the number of the antennas is used.the simulation results we had with the Matlab showed that for maximum data rate is almost twice with the increasing the signal to noise ratio, and  the  increasing in the number of the antenna elements of the compared with a tropospheric communications systems using one antenna.
Keywords: Channel Tropospheric; Troposcattering, Channel Capacity; Channel Simulation MIMO; Maximum data rate